The Arabs - Mansfield, Peter (Penguin Books, 1985)
The book explores social, political and historical aspects - from the pre-Islamic nomads of Arabia, the life of Muhammad and the rise of Arab power that followed, to the Western colonial period, the trategy of Palestine and the modern Arab renaissance, reinforced by the power of oil. The book shaws how the consequences of centuries of struggle for dominance between Christendom and the Islamic world survive to this day in various forms. An important section of the book surveys the Arab countries in gazetteer fashion. The final section considers the Arabs themselves, their characteristics, aspirations and their future